2019
DOI: 10.1007/s00232-019-00068-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Antimicrobial Lipopeptides with Bacterial Lipid Bilayers

Abstract: The resistance of pathogens to traditional antibiotics is currently a global issue of enormous concern. As the discovery and development of new antibiotics become increasingly challenging, synthetic antimicrobial lipopeptides (AMLPs) are now receiving renewed attention as a new class of antimicrobial agents. In contrast to traditional antibiotics, AMLPs act by physically disrupting the cell membrane (rather than targeting specific proteins), thus reducing the risk of inducing bacterial resistance. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 77 publications
6
24
0
Order By: Relevance
“…Figure S8 shows a rigidification clearly visible for PG and PS membranes, as expected. The increase of order observed upon peptide binding is not so uncommon, and depends on factors like lipid composition of the membrane, temperature, and charge [ 58 , 60 , 87 , 88 , 89 ]. Sometimes, peptides that attach to the surface of the bilayer can increase acyl chain packing [ 90 , 91 ], especially when a strong electrostatic attraction is established [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S8 shows a rigidification clearly visible for PG and PS membranes, as expected. The increase of order observed upon peptide binding is not so uncommon, and depends on factors like lipid composition of the membrane, temperature, and charge [ 58 , 60 , 87 , 88 , 89 ]. Sometimes, peptides that attach to the surface of the bilayer can increase acyl chain packing [ 90 , 91 ], especially when a strong electrostatic attraction is established [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rigidification effect upon binding is also consistent with the observed hydrophobic thickness ( Figure S9 ), that greatly increases for POPG, POPG containing membranes and CL as compared to POPC. Furthermore, the observed decrease in the electron density ( Figure S9 ) can be a consequence of more water molecules being located near the polar head groups due to more loosely packaging caused by the presence of the peptides [ 88 , 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their results demonstrated that POPE phospholipids have a higher diffusion coefficient than POPG. Additionally, it was found that there is a strong correlation between the choice of FFs and the simulation conditions with the calculated values for the lateral diffusion coefficients [200].…”
Section: Information Provided By the MD Simulationsmentioning
confidence: 88%
“…The order parameters of the pure POPE lipids match with the earlier simulation and experimental results. [37][38][39] The decrease in the order parameter is observed in both sn-1 and sn-2 chains. The decreasing S CD order parameter…”
Section: Deuterium Order Parameter (S CD )mentioning
confidence: 95%